Government's record on health services - Labour Party (Great Britain). Advisory Committee on Public Health
1927-09 1927 1920s 11 pages -4- £1,000 on dental treatment in elementary schools, and £500 on the treatment of physically defective children. In the Minutes of the Reading Education Committee, dated April 21st, 1927, one reads: Circular. 1388 - Your (Estimates) Section report that the amount of Grant which will probably be lost to the Committee during the year 1927-28 by reason of the application of the limits of the Circular 1388 to the Estimates of Income and Expenditure for that year is as follows :- (1) Elementary Education - (i) Administration and other expenditure - £146. (2) Higher Education - (i) Administration (including Reading School) - £166. (ii) Secondary Education and aid to students - £750 (approx.). But perhaps the greatest danger in Circular 1388 from the health point of view is to be found in the Clause dealing with Special Services; thus we read: "Special Services - Under this head the Board feel that the first aim of national policy should be the completion of the School Medical Service. It will be understood that the Board do not underrate the value of Special Schools, but while no rule can be laid down which is universally applicable to all areas and to all types of physical defect, the completion of the School Medical Service would appear to be of primary importance, and the Board suggest that Authorities should concentrate on this definite aim. With regard to provision for mentally defective children, Authorities will be aware that this very difficult problem is now being explored by a special committee, and save in exceptional circumstances, it would not seem prudent to incur heavy expenditure at the present moment on new schools for such children or on enlargements of existing schools." 292/840/1/15